1989
DOI: 10.1002/1097-0142(19891101)64:9<1968::aid-cncr2820640934>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum and outcome of microbiologically documentedListeria monocytogenes infections in cancer patients

Abstract: At the M.D. Anderson Cancer Center (Houston), Listeria monocytogenes was cultured from 14 patients between 1980 and 1987. The case records of 11 of these patients were reviewed. Underlying malignancies included acute leukemia (three), lymphoma (two), myeloma (one), adenocarcinoma of colon (two), carcinoma of breast (one), carcinoma of lung (one), and Kaposi's sarcoma associated with the acquired immune deficiency syndrome (one). Listeria monocytogenes was cultured from blood (eight patients), cerebrospinal flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 19 publications
1
5
0
1
Order By: Relevance
“…High mortality rates were observed after infection in cancer patients by Pseudomonas species [17,28,29], members of the family Enterobacteriaceae [17,20,23,25,26] and yeasts [15,16]. Other reports of the mortality associated with bloodstream infections are either not recent [21,31] or do not refer specifically to cancer patients [30–36] or are limited to a short period of observation [37,38]. However, in a 3‐year study of positive blood cultures, the rates of mortality after bacteremic episodes caused by various microorganisms were essentially the same as ours [37], with the highest percentages following infections caused by yeasts, Pseudomonas species, S. aureus and members of the family Enterobacteriaceae [37].…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…High mortality rates were observed after infection in cancer patients by Pseudomonas species [17,28,29], members of the family Enterobacteriaceae [17,20,23,25,26] and yeasts [15,16]. Other reports of the mortality associated with bloodstream infections are either not recent [21,31] or do not refer specifically to cancer patients [30–36] or are limited to a short period of observation [37,38]. However, in a 3‐year study of positive blood cultures, the rates of mortality after bacteremic episodes caused by various microorganisms were essentially the same as ours [37], with the highest percentages following infections caused by yeasts, Pseudomonas species, S. aureus and members of the family Enterobacteriaceae [37].…”
Section: Discussionsupporting
confidence: 51%
“…The mortality associated in cancer patients with blood infections caused by a single bacterial species has been frequently studied [17–29], but variations in the incidence of such infections over a period of time and in the associated mortality have not been reported. Furthermore, the trends in nosocomial primary bloodstream infections in the US between 1980 and 1989 have been published, but no emphasis was placed on the associated mortality [8].…”
Section: Discussionmentioning
confidence: 99%
“…Candida species have been isolated from patients with lower respiratory tract infection [7,20-22]. Haemophilus influenza [6,7,19-21], Staphylococcus epidermidis [6,7,17-19], Streptococcus species [6,7,17,19,25], Legionella pneymophila [23], as well as strains of Bacillus [7], Listeria [24] and Streptococcus [6,7,17,19,25] have been also identified in patients with different pulmonary diseases. Very similarly, the bacterium Chlamydia pneumoniae, a common cause of community-acquired pneumonia, has been implicated in lung carcinogenesis [11-16].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have demonstrated the presence of colonies in respiratory tract in patients with cancer [19]; Haemophilus influenza [6,7,19-21] and Candida albicans [7,20-22] have been found in patients with lower respiratory tract malignancies. Legionella pneymophila has been diagnosed in patients with cancer [23], as well as strains of Bacillus [7], Listeria [24], and Streptococcus [6,7,17,19,25]. …”
Section: Introductionmentioning
confidence: 99%
“…107,108,[120][121][122][123] Επίσης σε καρκινοπαθείς έχουν ανευρεθεί legionella pneumophila, τύποι βάκιλων, λιστέρια και στρεπτόκοκκοι. 124,107,108,118,120,125,126 Αξίζει να σημειωθεί ότι, προηγούμενες αναδρομικές και προοπτικές μελέτες προσανατολίζονταν σε ορολογική τεκμηρίωση χρόνιων βακτηριακών και μυκητιασικών φλεγμονών. 115 Για πρώτη φορά και μάλιστα σε αυτήν την εργασία διερευνώνται καρκινικοί πνευμονικοί ιστοί όσον αφορά την επικράτηση μικροβίων μέσα σε αυτούς.…”
unclassified